ANALYSIS OF CUSTOMER COMPARISON OF DAIHATSU TERIOS TYPES (XTRA, TX, TS) USING MULTIDIMENSIONAL SCALING METHOD - Wahani, Rezha Geovani; Pangemanan, Sifrid S. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: The current president of Indonesia, Mr. Joko Widodo  have a priority to build road infrastructure in order to create good economic improvement and management. with increased development in the transportation sector, it can be ascertained that growth in the automotive sector will increase rapidly, so this research will provide the result of the comparison of customer perception on Daihatsu Terios types using multidimensional scaling method. The purpose of this research is to figure out the similar different of Daihatsu Terios car with the same type. Based on this research, all of the respondent has their own perception about the similarity comparison to each type of Daihatsu Terios car and almost the student that used this type of Daihatsu Terios just care about the performance of the car, which is exterior and feature. Recommendation from researcher to the car company is to improve the exterior of each type of Daihatsu Terios to attract more customer from the 17-22 age range for more profit.Keywords: customer comparison, daihatsu terios, scaling method